Constitution, constitutional amendments and public policies: Unveiling government attention through constitutional changes - Brasil, Felipe Goncalves; Niedhardt Capella, Ana Claudia [UNESP]; Freitas Xavier de Souza, Lorraine Saldanha; Costa, Pedro Moura (Fundacao Getulio Vargas Escola Adm Empresas Sao Paulo, 2024)
From its enactment in 1988 until 2018, the Brazilian Federal Constitution underwent 105 changes through the approval of Constitutional Amendments. Given this high rate of amendments, this research aims to map and analyze the changes in the Constitution, focusing on the different types of sectoral policies targeted by these 105 amendments over 30 years. The study employs content analysis based on the Comparative Agendas Project (CAP) framework. The findings reveal that the Constitution expanded by more than 20% during this period. There was also an increase in policy regulations, particularly those aimed at guaranteeing various types of policies - primarily social policies - often at the expense of polity regulation. Finally, the conclusions highlight the importance of viewing the Federal Constitution as a locus for agenda formation, policy formulation, and the promotion of government priorities.
Keywords: government priorities. governmental agenda; Federal Constitution; Constitutional Amendments; policy dynamics; policy change